A Study on the Resolution and Depth of Focus of ArF Immersion Photolithography - Jungchul Song; Chae-Hwan Kim; Ga-Won Lee (Micromachines, 2022)
In this study, the resolution and depth of focus (DOF) of the ArF immersion scanner are measured experimentally according to numerical aperture (NA). Based on the experiment, the theoretical trade-off relationship between the resolution and depth of focus can be confirmed and k1 and k2 are extracted to be about 0.288 and 0.745, respectively. Another observation for a problem in small critical dimension realization is the increase in line width roughness (LWR) according to mask open area ratio. To mitigate the trade-off problem and critical dimension variation, the photoresist thickness effect on depth of focus is analyzed. Generally, the photoresist thickness is chosen considering depth of focus, which is decided by NA. In practice, the depth of focus is found to be influenced by the photoresist thickness, which can be caused by the intensity change of the reflected ArF light. This means that photoresist thickness can be optimized under a fixed NA in ArF immersion photolithography technology according to the critical dimension and pattern density of the target layer.